Transformation of the archetype of the trickster in contemporary Ukrainian art: on the example of the image of Hamlet - Turchyna, Mariia (Ukrainian Cultural Studies, 2022)
The article analyses the transformation of the archetype of the trickster in contemporary Ukrainian art on the example of the image of Hamlet. The concepts of "trickster", "culture hero" and "hero of culture", their meaning in archaic mythology and modern culture are considered. It was found that the archetype of the trickster is reflected in art through archetypal images – the trickster, a culture hero, which can exist both syncretically and separately. The common and distinctive features of the culture hero and hero of culture have been determined. At the end of the 20th century, the functions of a culture hero and a hero of culture are mixed, which contributes to the emergence of a "mass" culture hero, whose influence is determined to a greater extent not by qualitative indicators, but by quantitative ones. It was found that, the image of modern Hamlet in various cultural texts acquires trickster features. The transformation of the image of Hamlet in contemporary Ukrainian art is studied on the example of Yu. Andruhovich's translation "Hamlet, Prince of Denmark", L. Podervyansky's remake "Hamlet or the phenomenon of Danish Katsapism" and the horror opera "Hamlet" by R. Hryhoriv and I. Razumeyko. It was determined that in all three samples, rough, and sometimes obscene language is used, which translates the original text from a tragic into a farcical-comic discourse. It was found that there is a mixing of the features of a culture hero, a trickster, and a hero of culture in this image. Furthermore, it has been studied that the archetype of the trickster is transformed through the image of the trickster and the hero of culture. It is determined that, as a trickster, Hamlet provokes the overturning and rethinking of norms and rules. As a culture hero, he creates his own mythopoetic world in his mind. As a hero of culture, he personifies generally accepted patterns of behavior that positively correspond to a certain value-cultural system of society outside the mythological time-space.
Keywords: trickster archetype; trickster; culture hero; hero of culture; Hamlet